2020
DOI: 10.1111/epi.16535
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic laser anterior corpus callosotomy for Lennox‐Gastaut syndrome

Abstract: Objective: Corpus callosotomy is an effective palliative treatment for drug-resistant Lennox-Gastaut syndrome (LGS). Laser interstitial thermal therapy has been increasingly used in the treatment of epilepsy. Here, we assess the safety and effectiveness of minimally invasive stereotactic laser anterior corpus callosotomy (SLACC) for drop attacks in LGS. Methods: We reviewed sequential cases of patients with medically intractable LGS who underwent SLACC using a two-cannula technique between November 2014 and Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…10,11 MRgLITT offers significant advantages to open callosotomy, including its minimally invasive nature, shorter hospitalization and operative time, decreased total blood loss, and comparable seizure control rates. [11][12][13] Various studies have demonstrated LITT callosotomy as an effective therapy for reducing seizure rates in adult 12,[14][15][16][17][18][19][20][21][22] and pediatric 11,16,23,24 patients with drug-resistant epilepsy, with comparable effectiveness to open callosotomy. 11 This study presents experience performing MRgLITT callosotomy for the treatment of drug-resistant epilepsy characterized by drop attacks in pediatric patients at a tertiary academic center.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 MRgLITT offers significant advantages to open callosotomy, including its minimally invasive nature, shorter hospitalization and operative time, decreased total blood loss, and comparable seizure control rates. [11][12][13] Various studies have demonstrated LITT callosotomy as an effective therapy for reducing seizure rates in adult 12,[14][15][16][17][18][19][20][21][22] and pediatric 11,16,23,24 patients with drug-resistant epilepsy, with comparable effectiveness to open callosotomy. 11 This study presents experience performing MRgLITT callosotomy for the treatment of drug-resistant epilepsy characterized by drop attacks in pediatric patients at a tertiary academic center.…”
Section: Introductionmentioning
confidence: 99%
“…Corpus callosotomy is performed either as an anterior two-thirds disconnection of corpus callosum or as a complete disconnection [158], generally performed either through an open approach via a standard craniotomy with the aid of an operating microscope, or alternatively via a mini-craniotomy with endoscope assistance, with the latter having the benefit of a smaller incision, minimised brain retraction, and lower postoperative pain [158]. More recently, a minimally invasive method-magnetic resonance imaging (MRI)-guided stereotactic laser interstitial thermal therapy (LITT)-has shown promising results in case reports [159][160][161][162][163][164][165][166][167]. In the largest study to date, investigating MRI-guided stereotactic laser anterior corpus callosotomy (SLACC) in 10 patients with LGS (median age 33 years, range 11-52 years), eight (80%) patients had > 80% reduction in drop attacks, of whom five (50%) became free of drop attacks, and six (60%) achieved > 80% seizure reduction, with two (20%) becoming seizure free [167].…”
Section: Corpus Callosotomymentioning
confidence: 99%
“…More recently, a minimally invasive method-magnetic resonance imaging (MRI)-guided stereotactic laser interstitial thermal therapy (LITT)-has shown promising results in case reports [159][160][161][162][163][164][165][166][167]. In the largest study to date, investigating MRI-guided stereotactic laser anterior corpus callosotomy (SLACC) in 10 patients with LGS (median age 33 years, range 11-52 years), eight (80%) patients had > 80% reduction in drop attacks, of whom five (50%) became free of drop attacks, and six (60%) achieved > 80% seizure reduction, with two (20%) becoming seizure free [167]. In addition, the complications of SLACC were minimal (one asymptomatic tract haemorrhage and no cases of disconnection syndrome), and patients had short hospital stays and minimal postoperative discomfort.…”
Section: Corpus Callosotomymentioning
confidence: 99%
“…To reduce the invasiveness with craniotomy, stereotactic laser CC [ 15 , 16 ] and radiosurgical CC [ 17 ] have recently been developed. These techniques reportedly provide favorable seizure outcomes with low complication rates, comparable to the above-mentioned conventional CC with craniotomy.…”
Section: Surgerymentioning
confidence: 99%